2018
DOI: 10.1590/2177-6709.23.5.40.e1-9.onl
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal health knowledge and awareness among subjects with fixed orthodontic appliance

Abstract: Objective: To report on periodontal health knowledge and awareness among orthodontic patients and to investigate the effect of age, attitude and duration of orthodontic treatment on periodontal health awareness among orthodontic patients. Methods: A total of 297 orthodontics patient (90 males, 207 females) with mean age of 17.7 ± 5.0 years (older then 18 years = 119, 18 years or younger = 178) were included in this study. Subjects were currently wearing upper and lower fixed orthodontic appliances for an mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
22
1
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 26 publications
7
22
1
9
Order By: Relevance
“…In this study, among all study participants, female patients were more than male patients. Same results were seen in study by Al-harbi et al ,[12] Sharma,[14] and Alhaija et al [15] in which females were more than males to take up orthodontic treatment. This may be due to the fact that females were conscious about their looks.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In this study, among all study participants, female patients were more than male patients. Same results were seen in study by Al-harbi et al ,[12] Sharma,[14] and Alhaija et al [15] in which females were more than males to take up orthodontic treatment. This may be due to the fact that females were conscious about their looks.…”
Section: Discussionsupporting
confidence: 83%
“…Same results were reported in study by Al-harbi et al [12] in which majority of study participants had moderate awareness. In a study conducted by Alhaija et al ,[15] majority of the study participants had high level of awareness toward maintenance of periodontal health.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies observed a high percentage (>90%) of orthodontic patients brushing their teeth at least twice a day. [27][28][29]43 In comparison, other studies reported reduced adherence to toothbrushing (<65%). 26,30,33,34,37 These varying findings could be attributed to several reasons, such as differences in demographic factors or oral hygiene advice protocols implemented in the different countries and hospitals investigated in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…This distribution of gender is consistent with the literature and with the distribution of patients who attend orthodontic practice and seek orthodontic treatment. 24 , 26 , 27 , 29 , 30 This might be because females are more concerned about esthetics than males and have a higher demand for orthodontic treatment. 31 , 32 However, some studies reported different patterns of gender distribution, with more males undergoing orthodontic treatment than females.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, patients ongoing long treatment are more exposed to the potential accidents and complications inherent to orthodontics. It has been reported that longer orthodontic treatments have a negative impact on patients' attitude, especially when it comes to the maintenance of periodontal health (ALHAIJA et al, 2018) and the occurrence of caries (PINTO et al, 2018).…”
Section: Discussionmentioning
confidence: 99%